PENGARUH PENAMBAHAN AM 78 CAIR TERHADAP KUAT TEKAN BETON FC’ 19,3 MPA DENGAN KONDISI FAKTOR AIR SEMEN TIDAK TETAP - Asrullah, Asrullah; Anggraini, Rita; A, Herlian (Jurnal Teknik Sipil, 2023)
Concrete is a mixture of cement, coarse aggregate, fine aggregate, water and with or without additional ingredients (admixture) in a certain ratio which will form fresh concrete. Many studies have been carried out to find alternative uses for construction because concrete is a very important element, considering its function as one of the structures most widely used by society. Concrete is a mixture of cement, coarse aggregate, fine aggregate, water and with or without additional ingredients (admixture) in a certain ratio which will form fresh concrete. The advantages of concrete as a construction material include having high compressive strength, being able to follow the shape of the building freely, being resistant to fire and relatively cheap maintenance costs. The aim of this research is to determine the effect of adding Liquid AM 78 on the compressive strength of concrete Fc' 19.3 MPa under conditions where the cement water factor is not constant. The method used in the research is SNI 63-2834-2000 procedures for making normal concrete mixtures. The conclusion from the test results was that the compressive strength value of standard concrete (BS) aged 28 days was 19.40 MPa which was greater than the compressive strength of the planned concrete, namely 19.30 MPa and the highest compressive strength value of concrete with the addition of AM 78 Liquid 1.0% (B .1.0) 28 days old is 20.57 MPa.